Predictors of Online Health-Related Behaviors Among Healthcare Workers During COVID-19 Outbreak in Iran - Salmani, Fatemeh; Moshtagh, Mozhgan; Amiri, Rana; Moodi, Mitra (Health Nexus, 2023)
This study sought to identify the factors that influence online health-related behaviors among Iranian healthcare workers during the COVID-19 outbreak. The study utilized the Uses & Gratification and Self-Determination theories to explain the factors associated with workers’ behaviors and their use of social media to share information about the pandemic. A decision tree technique known as the Chi-Square Automatic Interaction Detector (CHAID) was used to analyze the responses of 406 participants. The results revealed that healthcare workers’ engagement in online health-related behaviors was primarily influenced by their attitude and motivation to use social media during the epidemic. Attitude was identified as the most important and first factor, while motivation was the second factor. The usefulness of information and interactions in the face of a health crisis can be linked to the development of self-efficacy and the promotion of social capital, as well as satisfaction with media. In conclusion, this study highlights the importance of understanding the factors that drive healthcare workers’ engagement in online health-related behaviors during a pandemic. The findings can be used to develop strategies to promote the use of social media for health-related purposes and improve healthcare workers’ response to future pandemics.